PENGARUH LEVERAGE, INTENSITAS PERSEDIAAN, INTENSITAS ASET TETAP, DAN PROFITABILITAS TERHADAP AGRESIVITAS PAJAK - Minar Savitri, Dhian Andanarini; Rahmawati, Ita Nur (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2017)
This study analyzes the factors that affect tax aggressiveness by comparing NPM companies with NPM industry. The sample used in this study is a manufacturing company listed on the BEI 2010-2015. Testing is done by logistic regression. The results showed that leverage, inventory intensity, and fixed asset intensity had no effect on tax aggressiveness. While profitability have a positive effect on tax aggressiveness.